2015
DOI: 10.1007/s40315-015-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics of the Energy of Sections of Greedy Energy Sequences on the Unit Circle, and Some Conjectures for General Sequences

Abstract: In this paper we investigate the asymptotic behavior of the Riesz s-energy of the first N points of a greedy s-energy sequence on the unit circle, for all values of s in the range 0 ≤ s < ∞ (identifying as usual the case s = 0 with the logarithmic energy). In the context of the unit circle, greedy s-energy sequences coincide with the classical Leja sequences constructed using the logarithmic potential. We obtain first-order and second-order asymptotic results. The key idea is to express the Riesz s-energy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In this work we focus on the particular case of the unit circle K = S 1 , and analyze in detail the asymptotic behavior of the extremal values U N,s (a N ) in (1.3), for all values of s > 0. Our results complement those obtained in [20], which described in this context the asymptotic behavior of the energies E s (α N,s ). We also refine the asymptotic formula (1.2) for the polynomials P n .…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this work we focus on the particular case of the unit circle K = S 1 , and analyze in detail the asymptotic behavior of the extremal values U N,s (a N ) in (1.3), for all values of s > 0. Our results complement those obtained in [20], which described in this context the asymptotic behavior of the energies E s (α N,s ). We also refine the asymptotic formula (1.2) for the polynomials P n .…”
Section: Introductionsupporting
confidence: 90%
“…In [2], Proposition 3.4 was proved for Leja sequences. But as it was remarked in [20], this result holds for greedy s-energy sequences as well, for any value of s > 0, since greedy s-energy sequences coincide geometrically with Leja sequences on S 1 . We now state this result in terms of greedy s-energy sequences on S 1 .…”
Section: By Symmetry This Impliessupporting
confidence: 57%
See 1 more Smart Citation
“…Pausinger [35] characterized the arising sequences (since there are often several maxima, there is an ambiguity in which one to pick and one can obtain several sequences); he also showed that this characterization also holds true for a larger class of notions of energy. Lopez‐Garcia and Wagner [34] established energy asymptotics. Götz [25], building on earlier machinery of Andrievski and Blatt [3, 4], Blatt [14], Blatt and Mhaskar [15], and Totik [45], proved that false∥DNfalse∥LN1/2logN.…”
Section: Statement Of Resultsmentioning
confidence: 99%
“…Introduction and statement of results. There are many studies related to the extremal problems for different kinds of energy of a discrete charge (see, e. g., the papers [2][3][4], [9], [10], [12], and the references therein). In contrast to the previous research, we consider the Green energy (see also the recent articles [1] and [5]).…”
mentioning
confidence: 99%